Fact the Reality of arranging the scout work in middle schools - Sabri, Khansaa (Journal of Physical Education, 2011)
((the research included five sections)) The first section \ Introduction and Problem: The importance of this study concentrate on the fact that organization is one entry for rising with the school scout is activity that has an important role in developing the abilities of the leaders in the way of directing them. The problem: through the researcher's viewing and her career in that field, the researchers do not tackled a study that have tackled the school scout work . for the importance of that work, and the basic problems from which schools are suffering in organizing the internal and external activities. The objectives: ** knowing the organizational problems from which the scout team suffer. ** suggest developed methods in organizing the scout teams. Hypothesis: ** there is no statistical differences in the factors effecting the study excellence for Teacher of physical education Rusafa 2. Second section\ the theoretical studies and similar studies: This chapter include a clear to the concept of organization, the elements of organization, importance of organization, and the steps to be followed when practicing scouting . Then we displayed similar studies. Section three\ the methodology and field procedures: This research include a descriptive methodology to cope with the problem in questions. Data were collected from the total community of study which included all the female students in the Teacher Preparation Institution Rusafa II for the morning classes, 113 students. In order to achieve the objective of the study, a questionnaire form was used as an instrument. Fourth Section: displaying the results The researcher displayed the results in tables and then illustrated them in forms to increase knowledge and to clarify them, and then the results were discussed after processing them. Fifth Section: Conclusions and Recommendations: Conclusions: The necessity of that encouraging female students by her family. Prepare all the capabilities that help students to memorize inside school and family. Necessity of organizing the reading time for the student. Recommendations: Making a similar study in the factors effecting genders (male, female). Making a similar study to know the effect of students excellence in the career of teaching